Question
upstudy study bank question image url

Question 7 Draw neat graphs of the functions on the same set of axes. Clearly indicate intercepts w the axes. \( f(x)=-x^{2}-2 x+3 \) \( g(x)=-2 \cdot 2^{x-1}+1 \)

Ask by Moran Medina. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

To graph the functions \( f(x) = -x^{2} - 2x + 3 \) and \( g(x) = -2 \cdot 2^{x-1} + 1 \) on the same set of axes, follow these steps: 1. **Graph \( f(x) = -x^{2} - 2x + 3 \):** - **Vertex:** At \( x = -1 \), \( f(-1) = 4 \). So, the vertex is at \( (-1, 4) \). - **x-intercepts:** Solve \( -x^{2} - 2x + 3 = 0 \) to find \( x = -3 \) and \( x = 1 \). - **y-intercept:** At \( x = 0 \), \( f(0) = 3 \). So, the y-intercept is at \( (0, 3) \). - **Shape:** Draw a downward-opening parabola passing through these points. 2. **Graph \( g(x) = -2 \cdot 2^{x-1} + 1 \):** - **Asymptote:** As \( x \) approaches negative infinity, \( g(x) \) approaches 1. - **Intercept:** At \( x = 0 \), \( g(0) = 0 \). So, the only intercept is at \( (0, 0) \). - **Additional Point:** At \( x = 2 \), \( g(2) = -3 \). Plot the point \( (2, -3) \). - **Shape:** Sketch an exponential curve that reflects vertically, shifts right by 1 unit, and up by 1 unit, approaching the asymptote \( y = 1 \) from below as \( x \) increases. 3. **Plotting on the Same Axes:** - Draw the coordinate axes. - Plot all intercepts and key points for both functions. - Draw the asymptote for \( g(x) \) as a dashed line. - Sketch both curves ensuring they reflect the described features. **Final Graph:** Both functions should be clearly labeled with their intercepts and the asymptote for \( g(x) \) should be indicated.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Bonus Knowledge

To graph the functions \( f(x) = -x^2 - 2x + 3 \) and \( g(x) = -2 \cdot 2^{x-1} + 1 \), first identify the intercepts for both functions. For \( f(x) \), set \( y = 0 \) to find the x-intercepts. Solving the quadratic equation \( -x^2 - 2x + 3 = 0 \) gives intercepts at \( x = 1 \) and \( x = -3 \). The y-intercept occurs when \( x = 0 \), yielding \( f(0) = 3 \). For \( g(x) \), find the x-intercept by setting \( y = 0 \), resulting in \( -2 \cdot 2^{x-1} + 1 = 0 \) or \( x = 2 \). The y-intercept is found at \( g(0) = -2 \cdot 2^{-1} + 1 = 0 \). Now, graph both functions on the same set of axes, marking the intercepts clearly for better analysis and comparison! With these graphs, you can visually analyze their behavior: \( f(x) \) is a downward-opening parabola, while \( g(x) \) is an exponential function that approaches the horizontal line at \( y = 1 \) as \( x \) increases. Enjoy drawing!

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy